Immunoglobulins G from Patients with Systemic Sclerosis Modify the Molecular Signatures of Endothelial Cells - Eric Hachulla; David Launay; Alain Lescoat; Valérie Lecureur; Vincent Sobanski; Sylvain Dubucquoi; Martin Figeac; Aurélien Chepy; Solange Vivier; Fabrice Bray; Clément Chauvet; Abderrahmane Elhannani; et al. (RMD Open, 2025)
Objective Antinuclear antibodies (ANA) are powerful biomarkers in systemic sclerosis (SSc). Functional antibodies (FA) might be implicated in vasculopathy, in which endothelial cells (EC) are key players. We aimed to explore the effect of purified IgG from patients with SSc on omics signatures of EC and examine the influence of ANA serotypes and FA.Methods EC were cultured in the presence of purified IgG from patients with SSc, patients with systemic lupus erythematosus (SLE) or healthy controls (HC). EC omics profiles were analysed by liquid chromatography with tandem mass spectrometry (LC-MS/MS) and RNA sequencing. EC proteome induced by IgG from patients with SSc was confirmed with an external validation cohort.Results In the derivation cohort, principal component analysis (PCA) using proteomics data showed three distinct groups of subjects: a first one including mostly anti-topoisomerase-I positive patients (ATA+), a second one including mostly anti-centromere positive patients and a third group comprising anti-RNA polymerase-III positive patients, SLE and HC. In transcriptomics, PCA distinguished one group composed of ATA+patients only from a second group mixing ATA+patients with other individuals. The validation cohort confirmed the existence of two groups of distinct EC proteome profiles and clinical severity in ATA+patients. In both SSc cohorts, no association between FA presence and proteomic profiles was observed. Quantitative proteomics measured the most discriminant proteins in EC exposed to purified IgG.Conclusion Purified IgG from patients with SSc can modify EC proteome and transcriptome. The observed changes closely associate with ANA serotype.